Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Small-Scale Patterns in the Distribution and Condition of Bamboo Coral, Keratoisis grayi, in Submarine Canyons on the Grand Banks, Newfoundland - Krista D. Baker; Paul V. R. Snelgrove; David A. Fifield; Evan N. Edinger; Vonda E. Wareham; Richard L. Haedrich; Kent D. Gilkinson (Frontiers in Marine Science, 2019)

Patterns and drivers of asteroid abundances and assemblages on the continental margin of A tlantic C anada - Katie S. P. Gale; Kent Gilkinson; Jean‐François Hamel; Annie Mercier (Marine Ecology, 2015)
Although continental shelf and slope environments typically exhibit high epifaunal biomass and have been subjected to increasing fishing pressure, ecological information on assemblages of non‐commercial invertebrate species from subtidal and bathyal areas remains limited. Sea stars (Echinodermata: Asteroidea), which are known to influence communities through their feeding habits, have received less attention than structural taxa such as corals and sponges. To better understand the ecological roles of asteroids on continental shelves, we investigated ~30 species and assessed their distributions and co‐occurrence with other benthic invertebrates on the shelf and slope of Eastern Canada. Using fisheries data and in situ video footage, we compiled a large dataset covering ~600,000 km 2 that included over 350,000 individual asteroid records (37–2243 m depth). Multivariate analyses revealed geographically distinct asteroid assemblages, with a maximal overall density at 400–500 m and the highest diversity at 500–700 m. The most abundant and densely occurring species was Ctenodiscus crispatus . We found that asteroids associate with corals, sponges, bivalves, and other echinoderms, and that depth and substrate influence these assemblages. We identified species likely to affect coexisting organisms by their burrowing behavior that can disrupt epi‐ and infauna ( C. crispatus ) and through predation on ecologically important corals ( Hippasteria phrygiana ). In addition to providing baseline distribution and ecological information for many bathyal asteroid species in the Northwest Atlantic, this work highlights the abundance and diversified roles of asteroids within continental shelf and slope ecosystems.

Feeding biology of Ophiura sarsii Lütken, 1855 on Banquereau bank and the effects of fishing - Jennifer L. Harris; Kevin MacIsaac; Kent D. Gilkinson; Ellen L. Kenchington (Marine Biology, 2009)